An RF Voltage Detector with Low Harmonic Feedback for Antenna Tuning Switches - Özdamar, Oguzhan; Hagelauer, Amelie Marietta; Weigel, Robert; Solomko, Valentyn (2019 IEEE International Conference on Microwaves, Antennas, Communications and Electronic Systems, COMCAS 2019, 2019)
A voltage detector with reduced harmonic feedback into the sensed RF path for the use in highly-linear, high-voltage antenna tuning switches is demonstrated. The reduction of harmonic content is achieved by adding linearization elements to the charge-pump-based rectifier, which are activated at large input RF voltage amplitudes. The detector has been implemented and tested in hardware with two high-voltage switches. The ICs were manufactured in Infineon 130nm RF switch process. The measured voltage detector exhibits a linear transfer characteristic and generates feedback harmonics level, which is below the nonlinearities of the intrinsic RF switch. The proposed detector targets voltage monitoring function, particularly in the RF switches for antenna tuning applications.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Antenna tuning; charge pump; harmonics; high-voltage switch; linearity; RF switch; voltage detector